A dinâmica socioeconômica dos libertos no contexto do alto império romano: a cena trimalchionis como estudo de caso - Silva, Cesar Roberto Melo [UNIFESP] (2016)
This thesis aims to analyze and discuss the socio-economic dynamics of freedmen in the context of the High Roman Empire. The research will be mediated from the scrutiny of Petronius's work, Satyricon, particularly in the episode Cena Trimalchionis. This source has the merit of presenting everyday features of a portion of the Roman society that does not appear in the works of the period very often, i.e., the one composed of the poor, the slaves, and, in particular, the freedmen. We aim to reflect on issues that make it possible to assess the place of those freed within the Roman society; their economic importance on that given social environment; and the relations of power in which they were inserted.